Sustainability of the utilization of biogas from sugarcane vinasse in electricity generation, transport fuel and natural gas substitution - Brandão, Carla Maia [UNESP] (2022)
Brazil is the second largest producer of fuel ethanol in the world, having produced 35.6 million m3 in the 2019/2020 harvest. The main by-product of this production process is vinasse, an aqueous solution that is generated at a rate of approximately 13.4m3 for every 1m3 of ethanol, resulting in around 477 million m3 of vinasse in the 2019/2020 harvest. Currently, the most common practice adopted by production units is the use of vinasse in fertigation of sugarcane fields to take advantage of its potassium content and consequent reduction in fertilizer costs. However, the high cost of transporting vinasse restricts its application only to the areas closest to the production units, causing negative environmental impacts. It is in this context that the anaerobic digestion of vinasse emerges as an interesting alternative since it enables the production of biogas and/or biomethane (purified biogas) through the conversion of the organic load of vinasse, maintaining the potassium content in the reactor effluent, but reducing its polluting potential. Thus, the objective of this work was to evaluate the possibilities of using the biogas or biomethane produced in a specific case study, designed to represent most of the existing ethanol production units in Brazil today. Considering historical average data from 171 sugarcane mills in the State of São Paulo (region with the highest concentration of production units in Brazil), a production unit with a crushing capacity of 2 million tons of sugarcane and about 448 m3 of ethanol per day, generating around 6,000 m3 of vinasse per day directed to the anaerobic reactor for biodigestion. The production of around 55,650m3 of biogas per day was studied in three different uses: directly, 1) for electricity generation through internal combustion engines; and after purification (36,173m3 of biomethane), 2) as a substitute for diesel oil in heavy vehicles and 3) as a substitute for natural gas. From the results obtained, it was concluded that: a) analyzing environmental issues in isolation, quantified through the economic gain generated by the sale of carbon credits, the use of biomethane as a substitute for diesel oil in heavy vehicles was the most advantageous option; b) analyzing social issues in isolation, quantified by the increase in purchasing power resulting from the generation of jobs, the use of biogas to generate electricity was the most advantageous option and c) analyzing economically, through the calculation of the net present value (NPV ), and jointly the technical issues (revenue generated by the sale of final products), environmental (revenue generated by the sale of carbon credits), social (increase in purchasing power resulting from the generation of jobs) and political/strategic (effect of tax credits on generated revenue), NPV<0 for electricity generation, NPV~0 as a substitute for diesel oil in heavy vehicles and NPV>0 as a substitute for natural gas, indicating that the injection of biomethane into the natural gas network was the most sustainable use among the three uses studied.